Tracing Knowledge in ”Langgher Seppo” - Azizah, Nur; As, Abdul Haq (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The present inquiry examines Langgher Seppo, an ancient prayer house established in 1769 AD by Bujuk Ajjih Habullah, which predates the official founding of Bondowoso Regency. As the symbolic foundation of Pesantren Poncogati—the oldest Islamic boarding school in the Besuki Residency—this site carries a profound historical trajectory from its origins as a center for santri lowo to its current status as a cultural landmark. This article seeks to analyze its historical evolution, its functional consistency amidst global transformations, and its enduring relevance within modernized educational frameworks. Utilizing a qualitative field research design, the investigation gathered data through observation, interviews, and documentation, ensuring validity via source and method triangulation. The analytical framework follows Miles and Huberman’s interactive model, encompassing data reduction, display, and verification. The findings reveal that Langgher Seppo transcends its role as a mere relic, serving as a vital identity marker that synthesizes traditional spirituality with contemporary educational needs. The current analysis offers a tripartite theoretical contribution: first, the Trisula of Langgher Seppo as a heritage site for knowledge dissemination; second, the Trisula Function, illustrating its role in formal, non-formal, and informal education; and third, the Trisula Holistic, which frames the site as an educational medium fostering intellectual, spiritual, and moral integrity. Ultimately, Langgher Seppo remains a strategic catalyst in the development of Islamic education within the era of globalization